Strategic analysis of the company Urdiamant, Ltd. - Matús, Eduard; Tyll, Ladislav; Tondlová, Markéta; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2013)
This thesis focuses on the topic of forming business strategies. In the theoretical part are summarized methodologies and tools that can be employed for evaluating and crafting competitive strategies in an environment where the only constant variable is change. The author discusses various approaches towards the strategy creation process, bearing the prescriptive school of thought as a cornerstone ideology. Goal of this thesis is to employ the acquired knowledge on a practical example of the company Urdiamant, s.r.o. One of this company's divisions serves as a subject for analysis and development of a feasible business strategy that would help the division in achieving a competitive advantage and creating an organizational structure and culture, which will enable adaptation to today's ever-changing environment without loosing the advantageous state.
Vedoucí práce: Ladislav Tyll
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2013
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2013
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses